FAKTOR-FAKTOR YANG MEMPENGARUHI KEPUASAN PELANGGAN DALAM BISNIS ONLINE - . Susilowati (Jurnal Komunikasi, 2015)
The increasing of Internet users in Indonesia proves that the strategy's implementation of Internet-based business can improve more rapidly, and expand the business competition in the virtual world or online business. The research aims to identify and examine the factors that affect customer satisfaction in the online business. The factors are  customer trust, product quality and price. Subjects were the customers in South Jakarta that have been doing online business transactions. The total sample is 100 respondents chosen using a non-probability sampling techniques. It is a quantitative research using case study methods and questionnaires. Data analysis techniques used  is multiple linear regression. Data collection tool is Likert scale as quantitative data and analyzed using descriptive analysis using SPSS software version 17.0 (statistical Package for the Social Science). The results showed that the Customer trust, Quality Products, Price, partially have a significant influence on customer satisfaction in online business, and simultaneously or together have a significant influence on customer satisfaction in online business. Based on the result, it is advisable to companies engaged in online business to increase customer trust, product quality, and price to be able to increase the customers' satisfaction in online business in the future. As well as other strategies need to be created to enhance competition in online business ventures, such as the aspects of improving the image and reputation of the company through advertising, as well as creating a brand image on the products shown in the companies' website. Keywords :  Customer  Trust , Quality Product, Price , Customer Satisfaction